Einverstanden, E. H. parteiinterne Hausmitteilungen, Briefe, Akten und Intrigen aus der Honecker-Zeit - Eberle, Henrik 1970- Hrsg; Wesenberg, Denise (Politik, 1999)
Parteiinterne Hausmitteilungen, Briefe, Akten u. Intrigen aus der Honecker- Zeit